An Analysis of the Significance of Vocabulary in Fostering ESL/EFL Students' Writing Skills: An Empirical Study - Dhuli, Raju; Lamo, Padma; Larsari, Vahid Norouzi (International Journal of Contemporary Studies in Education, 2023)
Writing skill is an important tool for academic success of any professional individual. This paper aims to analyze the indispensability of having vocabulary knowledge which in turn helps foster ESL/EFL students’ writing performance for their academic success. To this end, the researcher has gathered the past research papers in order to collect the important details of the relationship between vocabulary and writing skills. Moreover, this paper presented theoretical perspectives of vocabulary and writing. In a similar vein, the researcher detailed the students’ and researchers’ perceptions on the role of vocabulary in fostering skills of the ESL /EFL students. It also mentioned the results of the past studies that show the clear correlation between vocabulary and writing and their contribution to development of writing skills with the required amount of evidence. The conclusion provides some important points for ESL practitioners and students with respect to developing vocabulary knowledge.